Microwave-assisted synthesis, characterization and photoluminescence of shuttle-like BaMoO4microstructure - Anukorn Phuruangrat (2018)
© 2015 Wroclaw University of Technology. Shuttle-like BaMoO4microstructure has been successfully synthesized from Ba(N03)2·4H20 and Na2MoO4·2H2O as starting materials in ethylene glycol solvent containing 20 mL 5 M NaOH by microwave radiation at 180 W for 30 min. The as-synthesized BaMoO4product was characterized by X-ray diffraction (XRD), Fourier transform infrared (FT-IR) spectroscopy, Raman spectrophotometry, scanning electron microscopy (SEM), transmission electron microscopy (TEM) and photolumines-cence (PL) spectroscopy. XRD patterns revealed that the products was tetragonal BaMoO4phase. SEM and TEM characterization showed that the product had a shuttle-like BaMoO4microstructure. PL of the shuttle-like BaMoO4microstructure showed a maximum emission at 466 nm excited by 280 nm wavelength.